Clinical study on improving postoperative symptoms of cervical spondylotic myelopathy by Qishe pill. Issue 36 (4th September 2020) - Xu, Jinhai; Zhou, Xiaoning; Xu, Chen; Xu, Chongqing; Ding, Xing; Jin, Kun; Yan, Ming; Ma, Junming; Wu, Xuequn; Ye, Jie; Mo, Wen; Yuan, Wen
Abstract: Background: Cervical spondylotic myelopathy (CSM) is the most serious type of cervical spondylosis, which is often treated surgically in patients with progressive neurological symptoms following ineffective conservative treatment. However, some patients have residual symptoms such as neck pain, stiffness, and C5 nerve palsy after surgery. The Qishe pill can effectively relieve the symptoms of neck pain and numbness, but there is no evidence showing the efficacy and safety of the Qishe pill in treating symptoms after spinal cord surgery. Methods/design: A multicenter, randomized controlled clinical trial will be conducted to evaluate the efficacy and safety of the Qishe Pill. A total of 330 patients with CSM who receive surgical treatment will be randomly divided into 2 groups, treated for 12 weeks and with a 1-year follow-up. The primary outcome will be Japanese Orthopaedic Association score from the baseline to 4 weeks, 12 weeks, 24 weeks, and 48 weeks after surgery. Secondary outcomes will include Visual Analogue Scale score, Neck Disability Index, and imaging indicators (including magnetic resonance imaging and X-ray). Additionally, adverse reactions will be observed and recorded as safety indicators. Discussion: Although the Qishe pill can effectively improve the discomfort of the neck and upper limbs in clinical applications, there is a lack of clinical research on postoperative patients. This study will investigate the efficacy and safety of the Qishe pill in treating postoperative symptoms of CSM. Trial registration: Clinical Trials.gov ID: ChiCTR1900028173. Registered on 17 December 2019.